Analytic Study of Linear Analysis vs. Nonlinear Analysis: Optimum and Sustainable Structure Perspective (Sebha University Conference Proceedings, 2024)
This paper presents a comprehensive analysis of linear and nonlinear structural analysis methods, evaluating their Its effect in optimizing and sustaining structural designs. By leveraging advanced scientific data and analytical techniques, this study aims to discern the optimal conditions and scenarios for employing each method. The research includes detailed calculations, comparative data, and case studies, emphasizing the sustainability implications and long-term benefits of each approach.